Ageing in a non-heterosexual context. - Heaphy, B; Yip, A.K.T.; Thompson, Debbie (Cambridge University Press, 2004)
There is increasing recognition of the importance of social and cultural differences in shaping the diversity of the ageing experience in contemporary Britain. Various social and cultural factors, such as those associated with class, ethnicity, gender and disability, influence people’s living circumstances and sources of support in later life. While they have been the subject of considerable speculation, ageing in a non-heterosexual context remains remarkably under-studied. This paper examines the difference that being non-heterosexual makes to how people experience ageing and later life. It draws on quantitative and qualitative data gathered for a British study of the living circumstances of non-heterosexuals aged between the fifties and the eighties. Previous work has overwhelmingly emphasised how individuals manage their sexual identities, but this paper focuses on the factors that shape the non-heterosexual experience of ageing and later life. Particular attention is paid to the relational and community contexts in which non-heterosexuals negotiate personal ageing. This not only provides insights into the specific challenges that ageing presents for non-heterosexuals, but also offers insights into the challenges faced by ageing non-heterosexuals and heterosexuals in ‘ detraditionalised ’ settings.